Testosterone and benign prostatic hyperplasia - Jarvis, Thomas R (Asian J Androl, 2015)
The use of testosterone to treat the symptoms of late-onset hypogonadal men has increased recently due to patient and physician awareness. However, concerns regarding the effect of testosterone on the prostate, in particular any possible effect on the risk of prostate cancer have prompted further research in this regard. Surprisingly, numerous retrospective or small, randomized trials have pointed to a possible improvement in male lower urinary tract symptoms (LUTS) in patients treated with testosterone. The exact mechanism of this improvement is still debated but may have a close relationship to metabolic syndrome. For the clinician, the results of these studies are promising but do not constitute high levels of evidence. A thorough clinical examination (including history, examination and laboratory testing of testosterone) should be undertaken before considering the diagnosis of late-onset hypogonadism or instigating treatment for it. Warnings still remain on the testosterone supplement product labels regarding the risk of urinary retention and worsening LUTS, and these should be explained to patients.